Linear and generalized linear mixed models and their applications - Jiang Jiming (New York Springer-Verlag, 2007)
This book covers two major classes of mixed effects models, linear mixed models and generalized linear mixed models. It presents an up-to-date account of theory and methods in analysis of these models as well as their applications in various fields. It o
Keywords: Generalized linear mixed models; Linear models